‘The Anxiety of a Lifetime’—Dealing with Debt in Desistance from Crime - Gålnander, Robin (The British journal of criminology, 2023)
Debt problems are ubiquitous among people with convictions, yet debts’ implications for processes of desistance from crime remain underexplored. Existing research has primarily focused on ‘punishment debt’. Building on that, this longitudinal study of women in Sweden takes a holistic approach to debts in desistance. Debts are potentially criminogenic forces restricting agency in desistance. However, becoming debt-free and creditworthy is a potent way of approaching mainstream society from a position as ‘excluded other’. Importantly, while some debts are viewed as ‘normal’ and required to live out normative dreams of material prosperity, desisters perceived their debts as the ‘wrong’ type in relation to their view of normalcy. This emphasizes the long road toward the mainstream that desistance processes involve.